Bile negra: terrorismo, câncer e seus combates - Souto, Fhoutine Marie Reis (2015)
This work takes as a base the hypothesis that terrorism has been fought throughout history by the nations in a way akin to how Western medicine fights cancer, that unpredictable and unbearable disease that still has no definitive cure. Since its emergence in the end of the 19th century, terrorism this being the definition given by the world s states to violent struggles that endanger their wellbeing and existence has been targeted by procedures intent on physically eliminating it. However, just like tumors that strike again even after being extirpated, the diverse terrorist movements do not give u: The States have tried new treatments which, as radiotherapy and chemotherapy do when dealing with cancer, have a wide-ranging effect and intense, long-lasting side effects. When faced with the impossibility of a cure, both medicine and States invest in prevention and meticulous examinations to identify and eliminate potential threats still in formation. After over a century of fighting, both terrorism and cancer continue to manifest themselves. The victories are always individual, since as long as there is a State there will be terrorism just as cancer is a risk to everybody for as long as there s life, which remains ungovernable